A plea for standards in reporting data collected by animal-borne electronic devices. Issue 1 (December 2016) - Campbell, Hamish; Urbano, Ferdi; Davidson, Sarah; Dettki, Holger; Cagnacci, Francesca
Abstract In recent years, there has been significant investment in collaborative e-infrastructures to support biotelemetry research. Whilst these e-infrastructures are rapidly growing in size and sophistication, the current lack of standards for reporting and documenting the data collected by animal-borne telemetry devices is hampering their effectiveness. Here, we demonstrate why the current lack of standards is severely complicating the process for those developing and maintaining biotelemetry-related e-infrastructures, and provide suggestions as to how the current issue may be resolved. We hope this article will stimulate discussion across the community and facilitate the first steps towards the creation and adoption of industry standards for data collected by animal-borne telemetry devices.